A treatment protocol for infants younger than 1 year with acute lymphoblastic leukaemia (Interfant-99): an observational study and a multicentre randomised trial - Pieters, Rob; Schrappe, Martin; De Lorenzo, Paola; Hann, Ian; De Rossi, Giulio; Felice, Maria; Hovi, Liisa; LeBlanc, Thierry; Szczepanski, Tomasz; Ferster, Alice; Janka, Gritta; Rubnitz, Jeffrey; et al. (Lancet (London, England), 2007)
BACKGROUND: Acute lymphoblastic leukaemia in infants younger than 1 year is rare, and infants with the disease have worse outcomes than do older children. We initiated an international study to investigate the effects of a new hybrid treatment protocol with elements designed to treat both acute lymphoblastic leukaemia and acute myeloid leukaemia, and to identify any prognostic factors for outcome in infants. We also did a randomised trial to establish the value of a late intensification course. METHODS: Patients aged 0-12 months were enrolled by 17 study groups in 22 countries between 1999 and 2005. Eligible patients were stratified for risk according to their peripheral blood response to a 7-day prednisone prophase, and then given a hybrid regimen based on the standard protocol for acute lymphoblastic leukaemia, with some elements designed for treatment of acute myeloid leukaemia. Before the maintenance phase, a subset of patients in complete remission were randomly assigned to receive either standard treatment or a more intensive chemotherapy course with high-dose cytarabine and methotrexate. The primary outcomes were event-free survival (EFS) for the initial cohort of patients and disease-free survival (DFS) for the patients randomly assigned to a treatment group. Data were analysed on an intention-to-treat basis. This trial was registered with ClinicalTrials.gov, number NCT 00015873, and at controlled-trials.com, number ISRCTN24251487. FINDINGS: In the 482 enrolled patients who underwent hybrid treatment, 260 (58%) were in complete remission at a median follow-up of 38 (range 1-78) months, and EFS at 4 years was 47.0% (SE 2.6, 95% CI 41.9-52.1). Of 445 patients in complete remission after 5 weeks of induction treatment, 191 were randomised: 95 patients to receive a late intensification course, and 96 to a control group. At a median follow-up of 42 (range 1-73) months, 60 patients in the treatment group and 57 controls were disease-free. DFS at 4 years did not differ between the two groups (60.9% [SE 5.2] for treatment group vs 57.0% [5.5] for controls; p=0.81). During the intensification phase, of 71 patients randomly assigned to the treatment group, and for whom toxicity data were available, 35 (49%) had infections, 21 (30%) patients had mucositis, 22 (31%) patients had toxic effects on the liver, and 2 (3%) had neurotoxicity. All types of rearrangements in the (mixed lineage leukaemia) MLL gene, very high white blood cell count, age of younger than 6 months, and a poor response to the prednisone prophase were independently associated with inferior outcomes. INTERPRETATION: Patients treated with our hybrid protocol, and especially those who responded poorly to prednisone, had higher EFS than most reported outcomes for treatment of infant ALL. Delayed intensification of chemotherapy did not benefit patients.
Keywords: Leukemia, Myeloid, Acute; novorozenec; Infant, Newborn; cytarabin; Infant; Humans; methotrexát; kojenec; Cytarabine; následné studie; Prednisone; Methotrexate; protokoly protinádorové kombinované chemoterapie; lidé; prednison; Antineoplastic Combined Chemotherapy Protocols; akutní lymfatická leukemie; Precursor Cell Lymphoblastic Leukemia-Lymphoma; akutní myeloidní leukemie; Follow-Up Studies